EKSISTENSI PENGADILAN AGAMA DALAM MENGADILI PERKARA WARISAN - Mualifah Mualifah; Muhammad Faisal; Muhammad Jailani (Universitas Mataram, 2021)
Law No. 7 of 1989: “The Religious Court has the duty and authority to examine, decide and resolve matters in the first instance between Muslims in the field of marriage, inheritance, wills and grants made based on Islamic law and waqf and charity. The purpose in this study is to determine the application of Islamic inheritance law in resolving inheritance disputes in the Mataram Religious Court. The method used in this study is a normative legal approach that aims to analyze the decisions of religious courts related to inheritance cases. Aspects that will be studied are the application of Islamic inheritance law in the settlement of inheritance disputes and discrimination against women in Islamic inheritance law. The legal materials collected in this normative research are primary legal materials and secondary legal materials. The results show that as listed in article 49 paragraph 1 letter b, one of the